PENGARUH HEALTH EDUCATION TERHADAP PENINGKATAN PENGETAHUAN, SIKAP DAN PERILAKU LANSIA HIPERTENSI DI WILAYAH PUSKESMAS BINONGKO - Harmanto Harmanto; Jamuddin Jamuddin; Wa Ode Nurhidayah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Public knowledge about hypertension management is currently still lacking. Education is one way that can be used to increase one's knowledge. Education can be given in various fields, including health. The purpose of this research is to determine the effect of Health Education on increasing knowledge, attitudes, and behavior of the elderly with hypertension in the Binongko Community Health Center in 2022.This type of research is a quantitative method research that uses a pre-experimental design study with Pre-test and Post-test design treatment, a total sampling of 90 respondents with an analytical method using the Gain score (Sugiono 2018). The results of this study using the Wilcoxom test analysis, Knowledge was obtained at -8,132 and a significant value of 0.000 (p<0.05), Attitudes of -8.165 and a significant value of 0.000 (p<0.05), and Behavior of -8.267 and a value of -8.267. significant at 0.000 (p <0.05), there is a significant difference from the results of the pretest and posttest Health Education on the attitude of the elderly with hypertension in the Binongko Health Center area. These results prove that Ho is rejected and Ha is accepted, which means that there is an effect of Health Education on the attitude of the elderly with hypertension in the Binongko Health Center area. The conclusion is that there is an effect of Health Education on the knowledge, attitudes and behavior of the elderly with hypertension in the Binongko Health Center area.The suggestion of this research is that the puskesmas should do home care because some hypertensive elderly cannot check their health at the puskesmas due to limitations such as no family taking them to health services and busy with their daily activities such as gardening etc.